(untitled) (Journal of Contemporary Philology, 2022)
The purpose of this paper is to analyse the vocabulary used to talk about the COVID-19 situation in the Macedonian public space. For the purposes of this study a corpus of 130 Covid-19-related terms in English and their Macedonian counterparts was compiled. The English terms were extracted from the COVID-19 and SARS-CoV-2 Multilingual Terminology Collection found in the European Union terminology database (IATE), as well as other relevant COVID-19 glossaries. Their Macedonian counterparts were extracted from various public sources of information. The analysis is based on Vinay and Darbalnet’s (1958/1995 in Venuti 2000) model of translation strategies, complemented by some of Molina and Hurtado Albir’s translation techniques (2002). The analysis shows which translation strategies are used to convey COVID-19-related terms into Macedonian and how the terms relate to different audiences. The results stress the importance of conscious and effortful control over terminology adoption and creation.